PEMANFAATAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA PEMBELAJARAN EDITING VIDEO BAGI GENERASI Z - Suhartoyo, Armanda Rizky; Wulandari , Anita Agustina (DIGICOM : Jurnal Komunikasi dan Media, 2024)
In utilizing the latest technology through internet networks, people prefer smartphones as communication media tools due to their flexibility. The numerous features offered enable faster access to anything, such as the TikTok social media platform. Mostly, TikTok is a social media platform favored by Generation Z, who seek learning solutions through the utilization of TikTok, such as the desire to learn video editing. This research employs a qualitative descriptive research method. The results from the utilization of TikTok as a platform for learning video editing by Generation Z are that the conveyed information is more easily comprehended. The potential role of TikTok for Generation Z as a learning medium encompasses the available features on TikTok, the delivery methods of content creators, implementation, and collaboration. The obstacles faced in using TikTok for Generation Z as a learning medium include the lack of formal educational context and the inconsistent quality of content provided by content creators to Generation Z.